2013
DOI: 10.4322/acr.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid adenocarcinoma of the lung

Abstract: Lung adenocarcinomas with a mixture of tubular or papillary pattern, sheet-like or trabecular architecture, eosinophilic cytoplasm with centrally located nuclei and alpha-fetoprotein-producing cells have been described as hepatoid adenocarcinomas. Hepatoid adenocarcinomas are mainly found in the stomach but rare cases in other organs have been described. Immunostaining for alpha-fetoprotein (AFP), hepatocyte paraffin 1 (HepPar-1) and thyroid transcription factor-1 (TTF-1) helps in the diagnostic workup. Tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Most tumors have metastasized at diagnosis with a poor prognosis due to their aggressive behavior (1,2). Hepatoid adenocarcinoma(HAC) has been reported to occur in the stomach (3), esophagus (4,5), duodenum (6), jejunum (2), colon (7), peritoneum (8), pancreas (9)(10)(11)(12)(13), lung (14), ovary (15,16), gallbladder (17), uterus (16,18) and other sites (19). Of these locations, the stomach is the most common site of HAC.…”
Section: Introductionmentioning
confidence: 99%
“…Most tumors have metastasized at diagnosis with a poor prognosis due to their aggressive behavior (1,2). Hepatoid adenocarcinoma(HAC) has been reported to occur in the stomach (3), esophagus (4,5), duodenum (6), jejunum (2), colon (7), peritoneum (8), pancreas (9)(10)(11)(12)(13), lung (14), ovary (15,16), gallbladder (17), uterus (16,18) and other sites (19). Of these locations, the stomach is the most common site of HAC.…”
Section: Introductionmentioning
confidence: 99%
“…later named it as hepatoid adenocarcinoma of the stomach (HAS) [2] . HAC can occur in the stomach, intestine, pancreas, ovary, lung and other sites, among which the stomach is the most common site [3] , [4] , [5] , [6] , [7] . HAS accounts for 0.17%-15% of all gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only 34 cases of primary HAC lung have been reported in the world literature before December 2018. [3][4][5][6][7][8][9][10][11][12][13] Grossman et al reviewed 28 cases of HAC lung reported in the English literature, between January 1980 and June 2015. [5] Additional six case reports have been published from June 2015 to December 2018 including one Indian case report by Vellaisamy et al [3] In these reported 34 cases of primary HAC lung, 33 were males with age ranging from 36 to 77 years (mean 57 years).…”
Section: Discussionmentioning
confidence: 99%